ШЛЯХИ ПІДВИЩЕННЯ ЕФЕКТИВНОСТІ АДМІНІСТРАТИВНО-ПРАВОВОЇ ВІДПОВІДАЛЬНОСТІ ЗА ПРАВОПОРУШЕННЯ У СФЕРІ ЗЕМЕЛЬНИХ ВІДНОСИН В УКРАЇНІ - Музичук, Олександр Миколайович, Пахомов Володимир Васильович (SUPREMANCE OF LAW, 2017)
The essence of the administrative responsibility in the land relations sphere is reveal. Analyzes of the contemporary situation of legal ensuring of administrative responsibility in the land relations sphere in Ukraine were prepared. The directions of improvement of administrative and legal responsibility in the land relations sphere in Ukraine are offered.